Research and application of situated teaching design for NC machining course based on virtual simulation technology. Issue 3 (29th March 2020) - Li, Meng; Li, Yongxiang; Guo, Haixia
Abstract: As virtual simulation technology can display three‐dimensional materials as well as their dynamic cutting process and the learners' motivation is enhanced in the situated learning environment, a virtual‐situated learning system for numerical control (NC) machining course is proposed to explore the learning effectiveness of learners when combining virtual simulation technology and the situation learning theory. This study aims to use the concept of embedding NC machining simulation system and the situated learning into a real situation to improve the learners' situated thinking ability and innovative literacy. The features of the system include (a) the learning activities and contents that are planned and designed using the key factors of situated learning based on the specific teaching contents and objectives, (b) combining virtual objects with a real environment using virtual simulation technology to provide a project‐based learning situation for learners, and (c) probing into the specific methods of implementing situated teaching design in NC machining course. To assess the acceptance of the proposed system, an independent sample t ‐test was then applied to evaluate the learning achievement of learners. The results show that the research scale is highly reliable and that all assumptions made are valid. In addition, the effect of the situated teaching was investigated through questionnaire survey. The experimental results suggest that the virtual‐situated teaching design has significant positive impact on improving the students' learning efficiency and performance skills and indicates that the participants were attracted to and willing to use the system, which directly enhances their incentive to actively learn and promote learning achievement.